Chromium Tricarbonyl η6‐Complexes of [3]Cyclacene – A DFT Study. Issue 7 (17th January 2014) - Türker, Lemi
Abstract Chromium tricarbonyl η6 complexes of 3cyclacene are considered quantum chemically at the levels of B3LYP/6‐31G(d), B3LYP/6‐31++G(d, p), B3LYP/LANL2DZ, and RF/6‐31G(d, p)//B3LYP/6‐31++G(d, p). One of the complexes involves the top ring (A‐type) and the other one (B‐type) makes use of ring of the acene belt of the cyclacene in the complex formation. Energy calculations reveal that B‐type complex is more stable than A‐type. Some geometrical and quantum chemical properties were obtained. Additionally, vibrational and UV/Vis spectra of the complexes were produced.